14 films. box 1/3 [1969-2003] - Dwoskin, Stephen ([Genève] : Renard Films, 2006)
Disc 1. Take me (1969) -- Dirty (1965, 1971) / music, Gavin Bryars -- Girl (1971) -- Dad (2003) -- Grandpère's pear (c2003) -- Dear Frances (in memoriam) (2003). ## ##Disc 2. Pain is-- (c1997, original English version with English, French, German and Spanish subtitles) / ZDF/Arte, Urbane Limited, The Media Programme of the European Union, Les Films d'ici ; produced by Jane Weiner ; camera, Ian Wiblin, Stephen Dwoskin ; written and directed by Stephen Dwoskin -- Intoxicated by my illness (2001). ## ##Disc 3. Tod und Teufel = Death and Devil (1973, original German version with French, English and Spanish subtitles. Based on the play "Tod und Teufel" by Frank Wedekind ; Ein Q Production Film) -- Face Anthea (1990). ## ##Disc 4. Behindert (1973/74, original German/English version with French, English, German and Spanish subtitles) / Stephen Dwoskin and Carola Regnier ; direction and production, Stephen Dwoskin -- Outside in (1981, original English version with French, German and Spanish subtitles) / director, production, Stephen Dwoskin with Zweites Deutsches Fernshen [i.e. Fernsehen] ; camera, Robert Smith, Stephen Dwoskin, Bernard Trude ; editing, Brian Trenerry, Stephen Dwoskin ; production, Rebecca Dobbs, Madeleine Shaer ; script, Stephen Dwoskin ; music, Ben Mason. ## ##Disc 5. Trying to kiss the moon (c1994, original English version with English, French, German and Spanish subtitles) / an autobiographical film by Stephen Dwoskin ; assisted by Tessa Glover, Anthea Kennedy, Ian Wiblin ; music, Alexander Balanescu ; written, produced and directed by Stephen Dwoskin -- Lost dreams (2003).
French, English, German, Spanish subtitles
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Dwoskin, Stephen